Comparing lightning polarity and cloud microphysical properties over regions of high ground flash density in South Africa - Rautenbach, C.J. de W. (Cornelis Johannes de Wet) (University of Pretoria, 2014)
Dissertation (MSc)--University of Pretoria, 2013.